SUCCESFUL MANAGEMENT OF DYSTOCIA DUE TO PEROSOMUS ELUMBIS IN A HOLSTEIN FRIESIAN COW – A CASE REPORT - J, ARUNPANDIAN; J, DENY; N, SRIVASTAVA; S, GOVINDHASAMY; SIVAN G, ASWINI (The Indian Journal of Animal Reproduction, 2023)
A five-year-old female cow was presented to the Dharmapuri district veterinary clinic, Tamil Nādu with severestraining and ruptured first water bag. Per vaginal examination revealed incompletely dilated cervix, and foetal partswere not palpable. The treatment included induction therapy for further dilatation of cervix. The abnormality of thefoetal parts may lead to certain congenital anomaly. After thorough lubrication of the birth canal mild traction wasapplied to deliver the impacted fetus. The morphological appearance of the stillborn calf revealed that the conditionwas perosomus elumbis. The cow had an uneventful recovery.
Keywords: Cow; dystocia; perosomus elumbis; congenital anomaly